2021
DOI: 10.1038/s41598-021-89374-2
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic calcium responses in cultured antennal lobe neurons of the migratory locust

Abstract: Locusts are advantageous organisms to elucidate mechanisms of olfactory coding at the systems level. Sensory input is provided by the olfactory receptor neurons of the antenna, which send their axons into the antennal lobe. So far, cellular properties of neurons isolated from the circuitry of the olfactory system, such as transmitter-induced calcium responses, have not been studied. Biochemical and immunocytochemical investigations have provided evidence for acetylcholine as classical transmitter of olfactory … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Investigations on the distantly related, hemimetabolous locust could complement studies on holometabolous species and promote understanding of the general principles of insect immunity. The large size of locust hemocytes, and the recent discovery of a calcium sensor for locust cells [ 111 ] will enable us to study the role of calcium signaling in linking the immune stimulus to NO synthesis as a response. A further advantage of the locust is the large hemolymph volume and, thus, the large number of hemocytes that they share with other basal pterygotes.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations on the distantly related, hemimetabolous locust could complement studies on holometabolous species and promote understanding of the general principles of insect immunity. The large size of locust hemocytes, and the recent discovery of a calcium sensor for locust cells [ 111 ] will enable us to study the role of calcium signaling in linking the immune stimulus to NO synthesis as a response. A further advantage of the locust is the large hemolymph volume and, thus, the large number of hemocytes that they share with other basal pterygotes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the injection of calcium indicators for tracking the flow of calcium into a single pioneer neuron requires a time-consuming preparation of the embryo as a limb fillet [83]. Recently, we found that the next-generation calcium indicator dye Cal-520 AM could be bulk-loaded into locust neurons [95]. This technique has the potential for application to the intact embryo to visualize calcium signals in the pioneers.…”
Section: Limitations and Avenues For Future Improvementsmentioning
confidence: 99%